Urological Emergencies A Practical Guide - Wessells, Hunter; McAninch, Jack W. (Current Clinical Urology, 2005)
Because of changing patterns in health care delivery, the management of complex urological problems is increasingly taking place in hospital emergency rooms and the offices of primary care physicians, a trend that will be exacerbated by the anticipated shortage of urologists and a rapidly growing population of elderly people. In Urological Emergencies: A Practical Guide, practicing urologists summarize the optimal management of urgent and emergent urological conditions so that physicians with limited urological training can take advantage of the many recent improvements in the management of acute urological problems. Up-to-date, evidence-based descriptions of today's optimal diagnostic and therapeutic approaches cover a wide variety of conditions ranging from traumatic, infectious, and obstructive to hemorrhagic, iatrogenic, vascular, and congenital urological emergencies. The authors review the relevant pathophysiological background and epidemiology, recommend necessary diagnostic testing, and provide detailed medical, surgical, and endourological management approaches. These include advances in diagnostic testing and radiographic imaging, nonoperative treatment of acute injuries, and endoscopic and interventional techniques for obstruction, abscess, and bleeding. The chapters are organized by pathophysiology rather than organ system, so that the reader can quickly determine best-practice approaches based on the mechanism of the given disease. Comprehensive and user friendly, Urological Emergencies: A Practical Guide offers urology residents, practicing urologists, emergency medicine practitioners, trauma surgeons, and primary care providers without immediate access to urological consultation an invaluable resource ready for immediate bedside use.